CaLMo: A Tool to support the use of Causal Loop Diagram in Software Engineering - Apolinário, Amanda Brito; Lahass, Thiago Felippe Neitzke; Borges, Júlia de Souza; Santos Júnior, Paulo Sérgio dos; Barcellos, Monalessa P. (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2025)
Software organizations involve several processes, people, practices, culture, and other factors that affect their behavior. Understanding the organizational environment is crucial for improving processes and products. System Thinking (ST) can help in this matter. It views an organization as a system composed of elements and interconnections coherently organized in a structure that produces a characteristic set of behaviors. ST offers several tools, among which the Causal Loop Diagram (CLD) stands out. It represents feedbackdriven behaviors in complex systems and enables the visualization of organizational dynamics and the identification of systemic patterns. By understanding how the organization behaves, it is possible to identify problems and define actions aimed at improving products and processes. Currently, the creation of CLDs often relies on generic drawing/diagramming tools, which are prone to modeling errors and do not support the identification or analysis of behavior patterns. Additionally, most of these tools are limited to drawing the diagram and do not store the underlying represented data. To address this gap, this paper presents CaLMo, a tool designed to assist software engineers in modeling and analyzing CLDs to support Software Engineering tasks. CaLMo allows users to define variables, establish causal links between them, and detect feedback loops. Moreover, it automatically identifies archetypes that represent behavior patterns. We illustrate the use of the tool considering a case study in which CLDs were used to support the adoption of agile practices in an organization. A short video showing CaLMo is available at https://doi.org/10.5281/zenodo.15477387 .